2023
DOI: 10.1371/journal.pone.0282050
|View full text |Cite
|
Sign up to set email alerts
|

Network approaches and interventions in healthcare settings: A systematic scoping review

Abstract: Introduction The growing interest in networks of interactions is sustained by the conviction that they can be leveraged to improve the quality and efficiency of healthcare delivery systems. Evidence in support of this conviction, however, is mostly based on descriptive studies. Systematic evaluation of the outcomes of network interventions in healthcare settings is still wanting. Despite the proliferation of studies based on Social Network Analysis (SNA) tools and techniques, we still know little about how int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 116 publications
0
18
0
Order By: Relevance
“…This foundational knowledge can inform future work to understand the communication structure and its impact on the adoption of EBPs. Exploring these structures using SNA allows for the dynamics of the whole nursing unit to be examined, rather than only individual behaviors, which likely has more influence on the uptake of EBPs (Saatchi et al., 2023). This approach expands our knowledge of how to apply implementation strategies to improve EBP uptake and responds to the call for increased network analysis to generate nursing knowledge for a variety of topics, including EBP (Lee, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This foundational knowledge can inform future work to understand the communication structure and its impact on the adoption of EBPs. Exploring these structures using SNA allows for the dynamics of the whole nursing unit to be examined, rather than only individual behaviors, which likely has more influence on the uptake of EBPs (Saatchi et al., 2023). This approach expands our knowledge of how to apply implementation strategies to improve EBP uptake and responds to the call for increased network analysis to generate nursing knowledge for a variety of topics, including EBP (Lee, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Interest in SNA in health care has increased since the early 2000s (Glegg et al., 2019); however, its use in nursing studies has been limited (Kantek et al., 2022; Saatchi et al., 2023). A recent scoping review indicated approximately a dozen studies using SNA in nursing; various connection types including advice seeking, support, communication, and friendship ties were described (Saatchi et al., 2023). Few studies have explored the correlations between communication patterns of subgroups of nurses and specific patient outcomes, such as patient falls, medication errors (Brewer et al., 2018; Effken et al., 2011), hospital‐acquired pressure ulcers (Brewer et al., 2018), and patient satisfaction (Effken et al., 2011).…”
Section: Background and Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Effective prescribing therefore requires reassurance that weight gain will not escalate over and above that expected for the standard treatment approach (typically eating disorders focussed family therapy) and that the purpose of the medication is to moderate emotional arousal associated with the first phases of treatment to manageable levels, without inducing somnolence. This is based on the sedative, anxiolytic and mood-regulating effects of antipsychotics, which may enable them to reduce obsessive ideas and anxiety, improving mood stability (Thorey et al, 2023).…”
Section: Eating Disordersmentioning
confidence: 99%
“…While delineating the architecture of ordinary graphs—exemplified by pairwise node interactions represented by edges—has generated valuable insights in understanding and preventing health and safety risks, 101–103 it also comes with inherent constraints 104 . Like other complex networks (e.g., neural or metabolic systems), the multifactorial and multilayered nodes of this CANoN (i.e., the complex network of commercial drivers' health and safety risks) are anticipated to interact in larger groups and such interactions cannot be decomposed as linear combinations of dyadic couplings 105 .…”
Section: Commercial Drivers' Risks As Inclusive “Wholes”mentioning
confidence: 99%